An RNA interference screen identifies a novel regulator of target of rapamycin that mediates hypoxia suppression of translation in Drosophila S2 cells. - Lee, S.J.; Feldman, R.; O'Farrell, P.H. (Molecular Biology of the Cell, 2008)
In addition to its central role in energy production, oxygen has pervasive regulatory actions. Hypoxia (oxygen limitation) triggers the shutdown of major cellular processes, including gene expression. We carried out a genome-wide RNA interference (RNAi) screen in Drosophila S2 cells for functions required to down-regulate translation during hypoxia. RNAi knockdown of specific genes allowed induction of a green fluorescent protein (GFP) reporter gene and continued protein synthesis during hypoxia. Among the identified genes, Tsc1 and Tsc2, which together form the tuberose sclerosis complex that negatively regulates target of rapamycin (TOR) kinase, gave an especially strong effect. This finding is consistent with the involvement of TOR in promoting translation. Another gene required for efficient inhibition of protein translation during hypoxia, the protein tyrosine phosphatase 61F (Ptp61F), down-regulates TOR activity under hypoxia. Lack of Ptp61F or Tsc2 improves cell survival under prolonged hypoxia in a TOR-dependent manner. Our results identify Ptp61F as a novel modulator of TOR activity and suggest that its function during hypoxia contributes to the down-regulation of protein synthesis.